Comedic Cognition: The Impact of Elaboration on Political Comedy Effects. Issue 3 (27th May 2019) - Jennings, Freddie J.; Bramlett, Josh C.; Warner, Benjamin R.
Abstract : Political comedy has become an integral component of the political information environment. Though a great deal has been learned about the informative and persuasive effects of political comedy, the medium continues to evolve. John Oliver's Last Week Tonight presents heavily researched segments about issues that are often neglected in more traditional media. In the following study, we draw on the Elaboration Likelihood framework to argue that these long-form/low-salience segments challenge existing assumptions about the way people process political comedy. Specifically, we argue that effortful processing will enhance information acquisition and persuasion, that the social/sharing nature of the evolving media ecosystem will influence these effects, and that outcomes will be conditioned by an individual's affinity for political humor. Results from a randomized experiment support these conclusions.